Return On Assets Dan Ukuran Perusahaan Terhadap Pertumbuhan Laba Perusahaan Consumer Goods Tahun 2018 – 2021 - Jelita Anggraini; Muhammad Rivandi (Jurnal Riset Akuntansi, 2023)
Profit Growth is the change in the growth rate of revenue generated by a company. Profit growth is basically to recognize how much progress the company's achievements have achieved in a certain period of time. This study aims to find out and analyze how much influence Return On Assets (ROA) and Company Size have. The population in this study were consumer goods companies listed on the Indonesia Stock Exchange (IDX) in 2018 – 2021 which were selected using the purposive sampling method and obtained 29 consumer goods companies over a period of 4 years so that 116 samples were observed. The data analysis method used in this study is the panel data regression method. Based on the results of hypothesis testing, that Return On Assets (ROA) has a positive effect on profit growth and firm size has a negative effect on profit growth.